2016
DOI: 10.1038/srep27051
|View full text |Cite
|
Sign up to set email alerts
|

LPS/TLR4 Signaling Enhances TGF-β Response Through Downregulating BAMBI During Prostatic Hyperplasia

Abstract: Compelling evidence suggests that benign prostatic hyperplasia (BPH) development involves accumulation of mesenchymal-like cells derived from the prostatic epithelium by epithelial-mesenchymal transition (EMT). Transforming growth factor (TGF)-β induces EMT phenotypes with low E-cadherin and high vimentin expression in prostatic epithelial cells. Here we report that LPS/TLR4 signalling induces down-regulation of the bone morphogenic protein and activin membrane-bound inhibitor (BAMBI), which enhances TGF-β sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
(61 reference statements)
2
34
0
Order By: Relevance
“…However, it lacks the cytoplasmic kinase domain and is therefore generally thought to function as a negative regulator of both TGFβ and BMP signaling (Guillot et al, 2012;Tsang et al, 2000). In line with this, depletion of BAMBI expression reportedly enhances the TGFβ signaling response in cancer cell lines (He et al, 2016;Marwitz et al, 2016). Contrary data have also been reported, however, as high levels of BAMBI expression have been correlated with increased plasma TGF-β1 levels in chronic obstructive pulmonary disease patients (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…However, it lacks the cytoplasmic kinase domain and is therefore generally thought to function as a negative regulator of both TGFβ and BMP signaling (Guillot et al, 2012;Tsang et al, 2000). In line with this, depletion of BAMBI expression reportedly enhances the TGFβ signaling response in cancer cell lines (He et al, 2016;Marwitz et al, 2016). Contrary data have also been reported, however, as high levels of BAMBI expression have been correlated with increased plasma TGF-β1 levels in chronic obstructive pulmonary disease patients (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…It is noteworthy that toll-like receptor 4 (TLR4), a receptor for LPS which could enhance TGF-β signaling pathway, has been reported to play a key role in the process of organ fibrogenesis and LPS-induced EMT process (Guillot et al 2004;Seki et al 2007;He et al 2016;Tang et al 2018;Vidya et al 2018). And interestingly, previous studies implicated that cross talks exist between toll-like receptors and integrin αvβ6 (Pittet et al 2013;Jolly et al 2014), so integrin αvβ6 might be a therapeutic target for toll-like receptor-mediated fibrogenesis process.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of TGF‐β in prostatic stromal accumulation, which eventually leads to BPH, is well known , , . Aberrant activation of TGF‐β canonical signaling has been observed in both rodent and human prostatic hyperplasia , . Recent studies showed that the murine pan‐specific TGF‐β neutralizing monoclonal antibody, 1D11, had the effect of pharmacological inhibition of TGF‐β in different mouse models, including osteogenesis imperfecta , chronic nephropathy , and asthma .…”
Section: Discussionmentioning
confidence: 99%
“…High levels of transforming growth factor‐β (TGF‐β) activities are often observed in the pathogenesis of BPH . Induction of fibroplasia and collagenous micronodules was observed with TGF‐β1 overexpression in transgenic mice .…”
Section: Introductionmentioning
confidence: 99%